2020
DOI: 10.21203/rs.2.22405/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of zoonotic Enterocytozoon bieneusi genotypes in pre-weaned Korean native calves

Abstract: Background: Enterocytozoon bieneusi is the most common species of microsporidia that can infect humans and various animals worldwide. To date, information on the prevalence and genotypes of E. bieneusi infection in cattle in the Republic of Korea is limited. Therefore, in this study, we aimed to investigate the prevalence and genotypes of E. bieneusi circulating in pre-weaned Korean native calves and determine the age pattern of E. bieneusi infection and the relationship between E. bieneusi and diarrhea.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This is therefore of high public health significance. Findings also further demonstrate that human E. bieneusi infection is mainly related to animals [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This is therefore of high public health significance. Findings also further demonstrate that human E. bieneusi infection is mainly related to animals [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
“…The results of this study showed that 82.05% of genotypes belonged to Group 1. Group 1 has the largest number of species and is found in both domestic and wild animals worldwide [ 42 ], and is also the genotype group of E. bieneusi that mainly infects humans [ 31 , 32 ]. However, genotypes in other groups causing zoonotic disease cannot be ignored, such as J and BEBE4 in group 2, CAF4 and KIM3 in group 5, Nig3 and Nig4 in group 6, and S7 in group 10 [ 31 , 40 , 53 , 63 ].…”
Section: Discussionmentioning
confidence: 99%